Quo vadis DSM-6? An expert survey on the classification, diagnosis, and differential diagnosis of body-focused repetitive behaviors - Steffen Moritz; Luca Noemi Hoyer; Noam Sarna; Amitai Abramovitch; Cristian Curran; Alessandro S. De Nadai; Stella Schmotz (Comprehensive Psychiatry)
Background: Many conditions we now call body-focused repetitive behaviors (BFRBs) have been subject to research for several decades, most notably trichotillomania and skin picking. However, the American Psychiatric Association did not combine these conditions into a single category, body-focused repetitive behavior disorders (BFRBDs), until the fifth edition of the DSM (2013). Several aspects of the disorder remain uncertain and controversial. For example, ongoing debate surrounds which specific conditions fall under this diagnostic category and how to best differentiate BFRBs from conditions such as nonsuicidal self-injury (NSSI). The current article presents results from a survey of experts' opinions on diagnostic criteria, with the goal of refining the diagnostic criteria. Method: We contacted experts on BFRB via various sources and invited them to complete an online survey on the phenomenology, classification, and differential diagnosis of BFRB. We also inquired about possible alternative syndrome labels (e.g., body-focused habit). Results: Data from the final sample of 50 experts demonstrates that most experts agree with the present classification of BFRB/BFRBD as an obsessive-compulsive and related disorder and recommend retaining the labels BFRB or BFRBD. The experts considered the following conditions BFRB, with an agreement of over 60%: trichotillomania, skin picking, dermatophagia, nail biting, and lip-cheek biting. Mixed results emerged for awake bruxism and thumb sucking in adults. Only a minority regarded night bruxism and knuckle cracking as BFRB. To differentiate BFRB from NSSI, the experts noted that the motive behind the urge (self-harm/injury versus release of tension) should be considered. Analyses of a sub-sample of experts with at least six years of clinical and/or research experience yielded results compatible with those of the entire sample. Discussion: The survey supports the usefulness of the BFRBD diagnostic entity. However, some criteria require further refinement. Future editions of the DSM should more explicitly delineate which conditions qualify as BFRB. Furthermore, it is important to give more attention to the primary motivation behind BFRB to distinguish it from NSSI and potentially from stereotypic movement behavior.